Mapping the social landscape : readings in sociology - Ferguson, Susan J. (SAGE, 2021)
Summary: "Mapping The Social Landscape is one of the most established and widely-used readers for Introductory Sociology. The organization follows that of a typical introductory sociology course and provides coverage of key concepts including culture, socialization, deviance, social structure, social inequality, social institutions, and social change. Susan J. Ferguson selects, edits, and introduces 58 readings representing a plurality of voices and views within sociology. The selections include classic statements from great thinkers like C. Wright Mills, Karl Marx, and Max Weber, as well of the works of contemporary scholars who address current social issues. Throughout this collection, there are many opportunities to discuss individual, interactional, and structural levels of society; the roles of race, ethnicity, class, gender, and sexuality in shaping social life; and the intersection of statuses and identities."--Publisher